Bagassosis: A case report on rare hypersensitivity pneumonitis (Indian Journal of Case Reports, 2020)
Bagassosis is a rare form of occupational hypersensitivity pneumonitis (HP) caused by inhalation of bagasse. The incidence is significantly low after 1970 due to public awareness and an increase in organized sector industries. Being one of the largest sugar manufacturing countries and still the presence of industries in the unorganized sector, it is one of unnoticed diseases in some part of our country. In the present case, we describe the case of a 60-year-old male who presented with signs of respiratory failure. There was a history of occupational exposure to residuals of the sugarcane industry (bagasse) dust for the past 25 years with recent exposure before admission. The chest X-ray depicted bilateral opacity and computed tomography showed bilateral patchy opacities, septal thickening, and ground-glass opacities. His bronchoalveolar lavage revealed lymphocytosis. He was diagnosed as a case of bagassosis (occupation-related HP). He was admitted and treated with systemic corticosteroid and other supportive treatment and recovered gradually from respiratory failure. The treatment continued with a tapering dose of corticosteroid for the next 6 months, which improved him clinically, radiologically, and physiologically.